Rancang Bangun Prototype Mesin Pemotong Rumput Kendali Jarak Jauh Menggunakan Aplikasi Android - M. Khairul Amri Rosa; Reza Satria Rinaldi; Ridho Illahi (Universitas Bengkulu, 2019)
ABSTRACTThis research develops a prototype of a remotely controlled lawn mower using Android smartphone with Bluetooth connection to avoid the risk of accidents. The lawn mower is controlled by an Android application developed with Mit App Inventor using HC-05 Bluetooth module connection. This prototype uses a DC motor as a driving motor to rotate the blade with an LM393 speed sensor using Arduino Uno microcontroller. The developed system is equipped with an option of grass height that can be adjusted. The test of HC-05 Bluetooth module resulted the maximum acceptable connection distance in the open space is 80 m and the maximum connection distance with a barrier is 10.45 m. DC motor speed tests are carried out on the lawn mowers at no load and loaded conditions. The results showed a slight decrease in motor speed at the grass height of 6 cm and 4 cm, but at 2 cm height the rotation dropped significantly.Keywords: lawn mower, remote control, Arduino Uno, Bluetooth, Android